2006
DOI: 10.1113/jphysiol.2006.105510
|View full text |Cite
|
Sign up to set email alerts
|

Opposing role of synaptic and extrasynaptic NMDA receptors in regulation of the extracellular signal‐regulated kinases (ERK) activity in cultured rat hippocampal neurons

Abstract: The extracellular signal-regulated kinases (ERK) signalling cascade is a key pathway that mediates the NMDA receptor (NMDAR)-dependent neuronal plasticity and survival. However, it is not clear yet how NMDARs regulate ERK activity. Stimulation of the NMDARs induces a complex modification of ERK that includes both ERK activation and inactivation and depends on particular experimental conditions. Here we show that there exists a differential restriction in the regulation of ERK activity that depends on the pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
262
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(284 citation statements)
references
References 35 publications
19
262
1
2
Order By: Relevance
“…Synaptic vs extrasynaptic location of NMDARs critically alters receptor function and signaling pathway activation (Groc et al, 2009;Hardingham and Bading, 2010;Hardingham et al, 2002;Ivanov et al, 2006;Lau and Zukin, 2007). Extrasynaptic NR2B-containing NMDARs regulate NR2A function, potentially altering synapse development and plasticity (Kollen et al, 2008;Zhu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic vs extrasynaptic location of NMDARs critically alters receptor function and signaling pathway activation (Groc et al, 2009;Hardingham and Bading, 2010;Hardingham et al, 2002;Ivanov et al, 2006;Lau and Zukin, 2007). Extrasynaptic NR2B-containing NMDARs regulate NR2A function, potentially altering synapse development and plasticity (Kollen et al, 2008;Zhu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Total Versus Extrasynaptic NMDA Receptor Activation-To differentiate between activation of the entire pool of NMDA receptors and the extrasynaptic pool, we used a protocol initially developed by Hardingham's group (7,25). Briefly, for total NMDA receptor activation, cells were incubated for 3 min with 100 M NMDA, 10 M glycine, 1 M tetrodotoxin, 40 M 6-cyano-7-nitroquinoxaline-2,3-dione, and 5 M nifedipine after pretreatment with vehicle or 10 ng/ml PDGF-BB for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…PDGF␤ receptor activation enhances ERK1/2 phosphorylation in several systems via the recruitment of Grb2 scaffold proteins, via phosphatidylinositol 3-kinase, via activation of G␣ i , or after being transactivated by G-protein coupled receptors such as the D4 dopamine receptor (14,53). To investigate the potential of PDGF␤ receptors to alter NMDA signaling to ERK1/2 and CREB, we incubated 14 -21-day-old cultured hippocampal neurons with vehicle or PDGF-BB for 10 min, followed by stimulation of the total population of NMDA receptors or alternatively just the extrasynaptic population of NMDA receptors (25,53). In control hippocampal cultures, activation of all NMDA receptors did not alter CREB phosphorylation, however, after PDGF-BB treatment, NMDA treatment robustly enhanced phospho-CREB levels (Fig.…”
Section: Pdgf␤ Receptors Are Activated By Dimers Of the Isoform Pdgf-mentioning
confidence: 99%
“…According to this concept, it is not only the level of intra cellular calcium concentration that confers neuronal toxicity, but rather the Ca 2 + infl ux through NMDARs located outside the synapse. Moreover, several studies have demonstrated that some of the extrasynaptic signaling pathways dominate over effects of synaptic signaling, shutting off some important aspects such as cAMP response element-binding (CREB) protein and the extracellular signal-regulated kinase cascade (Ivanov et al , 2006 ). Conversely, for other authors, toxic stimuli through NMDARs are uniformly characterized by an obligatory link to massive mitochondrial Ca 2 + loading, whatever receptor location (Stanika et al , 2009 ).…”
Section: Nmdar Activation and Neuronal A β Synthesismentioning
confidence: 99%